Mixed boundary value problem for p-harmonic functions in an infinite cylinder - Björn, Jana; Mwasa, Abubakar (Nonlinear analysis, 2021)
We study a mixed boundary value problem for the p-Laplace equation Δpu=0 in an open infinite circular half-cylinder with prescribed Dirichlet boundary data on a part of the boundary and zero Neumann boundary data on the rest. Existence of weak solutions to the mixed problem is proved both for Sobolev and for continuous data on the Dirichlet part of the boundary. We also obtain a boundary regularity result for the point at infinity in terms of a variational capacity adapted to the cylinder.